The moderating role of age in the relationship between perceived over qualification, employability, job insecurity and global psychological needs satisfaction - Sabino, Ana (2022)
Purpose: This study aims to examine the relationship between perceived overqualification, perceived employability, perceived job insecurity and global psychological needs satisfaction, considering the moderating role of age groups. Design/methodology/approach: A cross-sectional survey design with a sample of 350 individuals was used in this study. Findings: A cross-sectional survey design with a sample of 350 individuals was used in this study. Originality/value: By addressing the moderating role of age, this study is original and has practical implications for age diversity management.